Descriptive analysis of the Finnish stock market: Part II - Peter Nyberg; Mika Vaihekoski (Bank of Finland, 2014)
This paper continues the data collection procedure and analysis set forth in Nyberg and Vaihekoski (2009). A number of new time series that are commonly used in finance literature are collected, created, and analyzed for the first time. These series include, among others, monthly dividend yields and market capitalization values. The series are also compared with GDP to evaluate the overall role of the stock market in the Finnish economy. The value-weighted average dividend yield from 1912 to 1988 is 4.98%. The average stock market capitalization to GDP ratio is found to be 15.14%.
URN:NBN:fi:bof-20140807220
Keywords: G10; G11; N24; 330; Stock market; financial history; dividend yield; capitalization values; trading turnover; Finland; Helsinki Stock Exchange; Nasdaq OMX